2016
DOI: 10.1007/s00442-016-3666-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic conservatism and climate factors shape flowering phenology in alpine meadows

Abstract: The study of phylogenetic conservatism in alpine plant phenology is critical for predicting climate change impacts; currently we have a poor understanding of how phylogeny and climate factors interactively influence plant phenology. Therefore, we explored the influence of phylogeny and climate factors on flowering phenology in alpine meadows. For two different types of alpine plant communities, we recorded phenological data, including flowering peak, first flower budding, first flowering, first fruiting and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 47 publications
4
30
2
Order By: Relevance
“…Consistent with the earlier study on the alpine plant community of Tibetan plateau, we found that budding, flowering, and initial fruiting were significantly aggregated across phylogenetically closely related Rhododendron species (Li et al. ). The opening of buds at the right time might consequently help plants to flower and fruit at favorable conditions when the pollinator availability is high, and also meet the required climatic conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the earlier study on the alpine plant community of Tibetan plateau, we found that budding, flowering, and initial fruiting were significantly aggregated across phylogenetically closely related Rhododendron species (Li et al. ). The opening of buds at the right time might consequently help plants to flower and fruit at favorable conditions when the pollinator availability is high, and also meet the required climatic conditions.…”
Section: Discussionsupporting
confidence: 92%
“…, Li et al. ), and snowfall (Forrest and Miller‐Rushing ) are the crucial factors influencing the timing of phenological events. Biotic factors such as the presence of pollinators and seed dispersers also serve as an important driver for staggering (Pleasants ) and aggregation of phenology events (Rathcke ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Li et al. ). Thus species tend to show large inter‐annual and spatial variation in flowering phenology.…”
Section: A Brief Introduction To Evolutionary Models In Community Phymentioning
confidence: 99%
“…Later in spring, sub-zero temperatures occur only occasionally, and summer flowering lowland species usually do not experience frost at all. As indicated above, patterns of flowering phenology in plant communities are the result of a long-term adaptation to environmental conditions [20]. Plant species that are not strictly controlled by day-length show a certain degree of phenological plasticity whereby onset and duration of flowering are primarily driven by temperature [21].…”
Section: Introductionmentioning
confidence: 99%